Efficacy of copper sulphate on Candida albicans on heat-polymerized acrylic resin. - Elisa Huerta; Daisy Gorup; Manuel Manríquez; Rodrigo Cruz Choappa; Peggy Vieille; Wilfredo González-Arriagada (Universidad de Concepción., 2020)
The ageing of population is increasing, and a great percentage of these patients wear removable prostheses, and can suffer denture stomatitis, a condition that has been associated with candidiasis. Aims: To evaluate in vitro the effectiveness of Copper Sulfate against Candida albicans in samples of heat-polymerized acrylic resin, compared to nystatin, sodium hypochlorite and chlorhexidine. Materials and Methods: Initially, the minimum inhibitory concentration (MIC) of copper sulfate for Candida albicans was determined by microdilution. Then, 54 resin samples were divided into 6 treatment groups corresponding to Nystatin 100.000 UI, Sodium Hypochlorite 0.5%, chlorhexidine 0.12%, Copper Sulfate 4.7µg/ml, Copper Sulfate 9.4µg/ml and physiological saline solution, in which samples were submerged for 6 hours. Resin samples were then washed and cultured on solid media at 37°C for 72 hours. The number of colony-forming units was determined using a Quebec colony counter. The statistical analysis was performed using the Kruskal-Wallis test and the Mann-Whitney U test. Results: Copper sulfate at a concentration of 9.4μg/ml presented a similar effectiveness as the other control products regarding the reduction in the number of colonies of Candida albicans post-treatment. Conclusion: The effectiveness of copper sulfate against Candida albicans on acrylic resin was similar to that of nystatin, sodium hypochlorite and chlorhexidine.